1998
DOI: 10.1111/j.1442-200x.1998.tb01894.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionized magnesium level in whole blood of healthy Japanese children

Abstract: Magnesium (Mg) catalyzes or activates more than 300 enzymes in the body, and it plays a pivotal role in the metabolism of carbohydrates, fats and proteins. Until recently Mg has only been measured as a total substance concentration; however, it is the free ionized form of magnesium (iMg2 + ) that is physiologically acti\.e. In 1092, a novel ion selective electrode (ISE) utilizing a neutral carrier-based membrane for essment of iMg2+ in whole blood, plasma or serum was designed and it was used to measure the iM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, only a few reports have measured iMg 2+ levels in children using the NOVA CRT8. One by Hoshiono et al involved 160 healthy Japanese children and found that the mean iMg 2+ level was 0.53 ± 0.03 (range: 0.45–0.63) mmol/L [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few reports have measured iMg 2+ levels in children using the NOVA CRT8. One by Hoshiono et al involved 160 healthy Japanese children and found that the mean iMg 2+ level was 0.53 ± 0.03 (range: 0.45–0.63) mmol/L [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of healthy volunteers, the mean whole blood ionized Mg concentration was 0·52 mmol/l with a range of 0·44 to 0·59 mmol/l and an ionized Mg/total serum Mg ratio of 0·60 and a range of 0·50–0·69 ( 78 ) . A positive correlation between ionized and serum total Mg was observed in 160 healthy children and the ratio was 58·3 ± 4·1 % ( 79 ) . There appears to be no demonstrable advantage to measuring ionized Mg as opposed to total Mg for evaluating Mg status.…”
Section: Tissuesmentioning
confidence: 99%
“…Our observation that serum Mg showed a significant correlation with age is consistent with previous reports of a relationship between age and serum Mg in healthy individuals. 23,24 Mg supplementation can increase bone density and arrest bone loss in osteoporotic patients 25 and its supplementation in children with ALL and hypomagnesemia is associated with a variable rise in serum Mg and a rise in osteocalcin levels. 6 It is possible that this variable response in serum Mg is age dependent and needs further exploration.…”
Section: Discussionmentioning
confidence: 99%